2022
DOI: 10.1159/000527181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bilastine on Chronic Urticaria: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> Allergic diseases are a public health problem with the largest number of patients and the widest age distribution. Chronic urticaria (CU) is a common clinical allergic disease. Bilastine is effective in the treatment of CU, especially skin wind masses and erythema. The purpose of this study was to systematically evaluate the efficacy and safety of Bilastine in the treatment of CU symptoms and to provide an evidence-based reference for clinical rational drug use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…), is an active antihistamine drug, sold under the trade name Bilaxten® for allergic rhinoconjunctivitis and chronic urticaria. [1][2][3][4] Repurposing drugs for the treatment of other chronic diseases including cancer is a recent technological niche to utilize the resources of 'active' pharmaceuticals for remedies with improved therapeutic responses and better pharmacokinetic profiles than that of existing drugs. 5,6 Previous reports in the literature have revealed the strong relevance of histamines to the regulation of several tumors such as cervical, ovarian, uterine, colorectal cancer and melanoma by promoting or inhibiting their growth.…”
mentioning
confidence: 99%
“…), is an active antihistamine drug, sold under the trade name Bilaxten® for allergic rhinoconjunctivitis and chronic urticaria. [1][2][3][4] Repurposing drugs for the treatment of other chronic diseases including cancer is a recent technological niche to utilize the resources of 'active' pharmaceuticals for remedies with improved therapeutic responses and better pharmacokinetic profiles than that of existing drugs. 5,6 Previous reports in the literature have revealed the strong relevance of histamines to the regulation of several tumors such as cervical, ovarian, uterine, colorectal cancer and melanoma by promoting or inhibiting their growth.…”
mentioning
confidence: 99%
“…This aligns with a meta-analysis underscoring bilastine’s efficacy in symptom control and QoL enhancement. [ 5 ] Nevertheless, morning administration may lead to heightened somnolence in the levocetirizine group. This study demonstrated that bilastine significantly alleviated physical discomfort from chronic idiopathic urticaria, and might enhance participants’ QoL and sleep.…”
mentioning
confidence: 99%